PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN BOOKLET TERHADAP KEMAMPUAN PEMECAHAN MASALAH DALAM MATERI LARUTAN PENYANGGA - Aryanti, Emilya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstrakThe purpose of this study is to determine the different of problem solving ability before and after applied problem solving learning model with booklet and the effect of the learning model to student class XI MIA MAN 2 Filial Pontianak. The study method that used is a pre-experimental design with a one group pretest posttest design. The study subject are students of class XI MIA MAN 2 Filial Pontianak. The data are collected by test and interview. Percentage of problem solving ability after learning with problem solving model with booklet show that student with very bad category 19,23%, bad category 46,15%, good category 30,77%, and very good category 3,85%. The result of analysis data using Shapiro-Wilk test show that the different problem solving ability before and after applied problem solving learning model with booklet. The effect size value result is shown that the effect of problem solving learning model with booklet through the problem solving ability in the amount of 5,2 with high category.Â Keywords: Problem Solving Ability, Problem Solving Model, Buffer SolutionÂ